FAST TRACK EXTUBATION IN ADULT PATIENTS ON PUMP OPEN HEART SURGERY AT A TERTIARY CARE HOSPITALFAST TRACK EXTUBATION IN ADULT PATIENTS ON PUMP OPEN HEART SURGERY AT A TERTIARY CARE HOSPITAL - Akhtar, Mohammad Irfan; Sharif, Hasanat; Hamid, Mohammad; Samad, Khalid; Khan, Fazal Hameed (Journal of Ayub Medical College Abbottabad, 2016)
Background: Fast-track cardiac surgery programs have been established as the standard of cardiac surgical care. Studies have shown that early extubation in elective cardiac surgery patients, including coronary and non-coronary open-heart surgery patients does not increase perioperative morbidity and mortality. The objective of this observational study was to determine the success and failure profile of fast track extubation (FTE) practice in adult open-heart surgical patients. Methods: The study was conducted at cardiac operating room and Cardiac Intensive Care Unit (CICU) of a tertiary care hospital for a period of nine months, i.e., from Oct 2014 to June-2015. All on pump elective adult cardiac surgery patients including isolated CABG, isolated Valve replacements, combined procedures and aortic root replacements were enrolled in the study. Standardized anesthetic technique was adopted. Surgical and bypass techniques were tailored according to the procedure. Success of Fast track extubation was defined as extubation within 6 hours of arrival in CICU. Results: A total of 290 patients were recruited. The average age of the patients was 56.3±10.5 years. There were 77.6% male and 22.4% female patients. Overall success rate was 51.9% and failure rate was 48.1%. The peri-operative renal insufficiency, cross clamp time and CICU stay (hours) were significantly lower in success group. Re-intubation rate was 0.74%. Conclusion: The perioperative parameters were significantly better in success group and the safety was also demonstrated in the patients who were fast tracked successfully. To implement the practice in its full capacity and benefit, a fast track protocol needs to be devised to standardize the current practices and to disseminate the strategy among junior anaesthesiologists, perfusionists and nursing staff. Keywords: Fast Track Extubation; Adult; Open-heart surgery